PENTINGNYA PENDIDIKAN INKLUSIF BAGI ANAK BERKEBUTUHAN KHUSUS - Frans Laka Lazar (Jurnal Pendidikan dan Kebudayaan Missio, 2020)
Inclussive education means that all students including child with special needs attend, participate, and learn in inclussive schools with normal students without considering each disabilities. The aim of this article is to describe the importance of inclusive education for child with special needs, because the reality shows to us that many students with special needs often times did not get the same educational treatment fairly like normal students. This article helps people open the understanding and horisan of the right of every citizen especially child with special needs to get the same education with normal students. In order to reach out this aim, the writer applies library research method in which he reads and writes the material related to this topic from the articles, journals, and books. The results of the study pointed out that some parents and the socities did not undertand much the urgency of inclusive education for child with special needs. Therefore, child with special needs often time did not get the same right in relation to education like normal childen.